Single-reactor tandem oxidation–amination process for the synthesis of furan diamines from 5-hydroxymethylfurfural. Issue 18 (23rd August 2021) - Sha, Jin; Kusema, Bright T.; Zhou, Wen-Juan; Yan, Zhen; Streiff, Stephane; Pera-Titus, Marc
Abstract : A single-reactor tandem oxidation–amination process was engineered with bifunctional RuPd/C catalyst for the synthesis of secondary furan diamines. Abstract : We present an efficient and intensified single-reactor tandem process accessing a library of secondary furan diamines from HMF. The process comprises two in situ consecutive steps: (1) aerobic oxidation of HMF to DFF, and (2) reductive amination of DFF to diamines. The reactor was operated using a mechanical mixture of 5%Ru/C + 5%Pd/C catalysts with more than 87% overall yield of diamines. With these results, a bifunctional (Ru + Pd)/C catalyst was engineered with comparable results to the mechanical mixture.